Features of tumor texture influence surgery and outcome in intracranial meningioma. Issue 1 (10th September 2020) - Sauvigny, Thomas; Ricklefs, Franz L; Hoffmann, Lena; Schwarz, Raphael; Westphal, Manfred; Schmidt, Nils Ole
Abstract: Background: Texture-related factors such as consistency, vascularity, and adherence vary considerably in meningioma and are thought to be linked with surgical resectability and morbidity. However, data analyzing the true impact of meningioma texture on the surgical management is sparse. Methods: Patients with intracranial meningioma treated between 08/2014 and 04/2018 at our institution were prospectively collected for demographics, clinical presentation, histology, and surgical treatment with related morbidity and extend of resection. Tumor characteristics were reported by the surgeon using a standardized questionnaire including items such as tumor consistency, homogeneity, vascularization, and adherence to surrounding neurovascular structure and analyzed for their impact surgical outcome parameters using univariate and logistic regression analyses. Results: Tumor texture-related parameters of 300 patients (72.3% female) with meningioma were analyzed. Meningioma localizations were grouped into 3 different cohorts namely convexity, skull base, and posterior. Postoperative occurrence of a neurological deficit (transient 23.0%; permanent 6.1%) was associated with the duration of surgery ( P = .001), size of tumor ( P = .046), tumor vascularization ( P = .015), and adherence to neurovascular structures ( P = .002). Coherently, the duration of surgery (mean 230.99 ± 101.33 min) was associated with size of tumor ( P < .0001), vascularization ( P < .0001), and adherence ( P < .0001). Similar associations were recapitulated in subgroup analyses of different tumor localizations. Noteworthy, tumor rigidity had no significant impact on time of surgery and neurological outcome. Conclusions: Our analysis demonstrates that tumor texture has an impact on the surgical management of meningioma and provides data that tumor vascularization and adherence are significant factors influencing surgical outcome whereas the influence of tumor consistency has less impact than previously thought.